Building A Law-Aware Society: The Role of The Law and Human Rights Service Division of The Ministry of Law And Human Rights of North Sumatra, Indonesia - Simarmata, Prayusti Sarah; Simamora, Janpatar (Golden Ratio of Data in Summary, 2025)
Law grows from community traditions which develop into customary law, providing the basis for justice and law enforcement in society. The aim of the law is to create peaceful and fair interactions, and to achieve this it must be respected and obeyed, which requires public awareness and involvement in law enforcement. Community legal awareness means understanding, obeying and complying with the law. In North Sumatra, the Ministry of Law and Human Rights plays an important role in fostering legal awareness through the "North Sumatra Thinking Concept: Awareness of Law and Human Rights." This concept begins with the formation of a Legally Aware Family (Kadarkum), which aims to increase the community's understanding and compliance with legal norms. Kadarkum is also supported by the Legal Awareness Village (DHS) initiative, which helps foster a legally aware society.